UJI EFEKTIFITAS BIOLARVASIDA EKSTRAK ETANOL BUAH LAMPESU (Baccaurea lanceolata) TERHADAP LARVA INSTAR III Culex quinquefasciatus - Dea Alfani Nandjan (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2020)
Filariasis is chronic infection disease caused by worm and carried by Culex quinquefasciatus mosquito. One of theways to controlling mosquitoes vectors are use biolarvacide or chemical insecticide. Chemical insecticide causingresistance Culex quinquefasciatus larvae and toxic for human. This research aim to determine the biolarvacideeffectiviteness of ethanol extract lampesu fruit (Baccaurea lanceolata) to Culex quinquefasciatus larvae instars III.This study was true experimental with a Post test-only control group design. This study used 700 larvae instars III ofCulex quinquefasciatus divided into 7 groups consentration of 0,2%, 0,4%, 0,6%, 0,8% and 1%, the positive control(abate) and negative control (aquadest). The observation was did after treatment in 3 hours, 6 hours, 12  hours and 24hours. The experiment is replicated four times. At 24 hours exposure concentration of 0,6% the test larvae mortalityreached 38% and at concentration of 1% the test larvae mortality reached 30%. In this stuy the concentration of1,531 % was effective to kill larvae with of 50% mortality(LC50) and concentration of 10,729 % was effective to killlarvae with of 90% mortality(LC90). Ethanol Ekstract of Lampesu Fruit (Baccaurea lanceolata) not effective asbiolarvacide ofCulex quinquefasciatus larvae instars III.